PENYULUHAN DAN PELATIHAN ICT-ENHANCED TEACHING –LEARNING SEBAGAI MODEL PENGEMBANGAN PROFESIONAL GURU DI KOTA BENGKULU - Azwandi, Azwandi; Harahap, Alamsyah; Syafryadin, Syafryadin (Vokasi Universitas Halu Oleo, 2019)
The use of ICT in learning is rarely found particularly in areas with low literacy. Like a high school teacher at Bengkulu City, they do not use ICT in learning, especially they whom with over the age of 40 years old. The lact of fasilitators also make difficult to reach innovative learning with high quality. Thus, It absolutely needs counseling and training on ICT. This training aims not only to give guidance on ICT, but also to move the teachers for using ICT as a medium of professional learning in their class routines. This training used the method of lectures, discussions and practice with the participatns of 20 teachers at Anggut Atas Village, Gading Cempaka District, Bengkulu City on all subjects. The results of this training indicated that the use of ICT on learning suach as Mobile-Asissted Language Learning (MALL) ataupun Computer-Assisted Language Learning (CALL) could be received and actualized by the teachers at Anggut Atas Village, Gading Cempaka District, Bengkulu City. This training can be concluded that implementation of ICT with the existance of facilitators are very needed in developing innovative and efficient learning with high quality.